The Role Of Quality, Promotion And Trust In Purchase Decisions At PT. Weedo Niaga Global - Syaifullah; Ester Hervina Sihombing; Maya Andriani; Sabaruddin Chaniago; Manda Dwipayani Bhastary (International Journal of Science, Technology & Management, 2021)
In this era of globalization and technology, there is a demand for changes in all areas of business in the world today. One of them is in the field of marketing. The development of the information technology system which is growing rapidly and increasingly sophisticated has made the company take advantage of the marketing and selling interests of its products. This research aims to examine the effect of product quality, promotion and trust on purchasing satisfaction at PT Weedo Niaga Global both partially and simultaneously. This study used a descriptive research design with a quantitative approach. The software used to manage and analyze this data is SPSS version 25. The sample was determined using random sampling of 115 respondents. Data collection was carried out by means of a questionnaire. Based on the results of statistical tests, it is known that the variables of product quality, promotion, trust and purchase decisions are normally distributed data, the independent variables do not occur multicollinearity and heteroscedasticity. From the results of the determination coefficient of 51.7%. The t test results show that the value of product quality is 3.239> 1.98118 with sig 0.002 <0.05 means that product quality has a positive and significant effect on purchasing decisions, the promotional value of 5.454> 1.98118 with sig 0.000 <0.05 means that promotion has a positive and significant effect on purchasing decisions, and the value of trust 2.983> 1.98118 with sig 0.004 <0.05 means that trust has a positive and significant effect on purchasing decisions. While the f test results show the value of 39,581> 2.69 with sig 0.000 <0.05, so simultaneously the variables of product quality, promotion and trust have a significant effect on purchasing decisions.